(untitled) (Jurnal EurekaMatika, 2025)
Abstract Artificial Neural Network (ANN) is one of the popular methods used to predict time series data. ANN has the advantage of being able to handle nonlinear patterns in the data, making it more adaptive in predicting than conventional methods. Backpropagation is an ANN algorithm used in multilayer networks with a supervised training method. This research utilizes the Backpropagation method in ANN to predict the number of foreign tourist visits to Indonesia. The data used includes the number of such visits from January 2008 to December 2024. The results show that the ANN (12-9-1) model is the most superior model in predicting the number of foreign tourist visits to Indonesia. The ANN (12-9-1) model obtained a MAPE value of 10.02% at the model performance testing stage, meaning that the ANN (12-9-1) model is able to produce good predictions. Keywords: ANN, Backpropagation, Prediction, The number of foreign tourist visits Abstrak Artificial Neural Network (ANN) adalah salah satu metode yang popular digunakan untuk memprediksi data deret waktu. ANN memiliki keunggulan mampu menangani pola nonlinier di dalam data, sehingga lebih adaptif dalam memprediksi dibandingkan metode konvesional. Backpropagation merupakan algoritma ANN yang digunakan pada jaringan multilayer dengan metode pelatihan terawasi. Penelitian ini memanfaatkan metode Backpropagation pada ANN untuk memprediksi jumlah kunjungan wisatawan mancanegara ke Indonesia. Data yang digunakan mencakup jumlah kunjungan tersebut dari Januari 2008 hingga Desember 2024. Hasil penelitian menunjukkan model ANN (12-9-1) merupakan model yang paling unggul dalam memprediksi jumlah kunjungan wisatawan mancanegara ke Indonesia. Model ANN (12-9-1) memperoleh nilai MAPE sebesar 10.02% pada tahap pengujian kinerja model artinya model ANN (12-9-1) mampu menghasilkan prediksi yang baik.